∫ − ∞ ∞ x e 3 x e − e 2 x d x
If the above Integral can be expressed as B π A / 2 ( C − γ − D ln ( E ) ) ,
where A , B , C , D , E are positive integers, with E prime, find A + B + C + D + E .
Notation : γ denotes the Euler-Mascheroni constant , γ = n → ∞ lim ( − ln n + k = 1 ∑ n k 1 ) ≈ 0 . 5 7 7 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Do you know how to derive the value of ψ ( 2 1 ) ?
Log in to reply
Google it.
Log in to reply
I know how. i just wanted you to add that in your solution for users.
@Aditya Kumar : @Aareyan Manzoor
Ψ ( x ) = d x d ln Γ ( x ) = Γ ( x ) Γ ′ ( x )
Log in to reply
Wow! Thanks for the new knowledge! I didnt know that, i just knew how to apply it. You know sometimes you know how to apply stuff before defination. i also know Γ ′ = ψ Γ but not that defination.
All sarcasm aside, i actually learned later how to calculate it. Do the integral ψ ( 1 / 2 ) = − γ + ∫ 0 1 1 − x 1 − x − 1 / 2 dx The integral is easy.
Log in to reply
@Aareyan Manzoor – I am glad that you found it useful...:)
Problem Loading...
Note Loading...
Set Loading...
Substitute 1 0 e 2 x = t → x = 2 ln ( t ) d t = 2 e 2 x d t ∣ − ∞ ∞ → ∣ 0 ∞ The integrand becomes: 4 1 ∫ 0 ∞ ln ( t ) t 1 / 2 e − t dt Consider the gamma functions: Γ ( a ) = ∫ 0 ∞ t a − 1 e − t dt d.w.r.a Γ ′ ( a ) = ∫ 0 ∞ ln ( t ) t a − 1 e − t dt put a=3/2 to get that Γ ′ ( 3 / 2 ) = ψ ( 3 / 2 ) Γ ( 3 / 2 ) = ( 1 / 2 1 + ψ ( 1 / 2 ) ) 2 1 Γ ( 1 / 2 ) = 2 π 1 / 2 ( 2 − γ − 2 ln ( 2 ) ) we know ψ ( 1 / 2 ) = − γ + ∫ 0 1 1 − x 1 − x − 1 / 2 dx = − γ − 2 ln ( 2 ) final answer is ∫ − ∞ ∞ x e 3 x e − e 2 x d x = 8 π 1 / 2 ( 2 − γ − 2 ln ( 2 ) )